Ride through testing of variable speed drive due to voltage sag types (types I, II and III) - Surya Hardi; R. Harahap; S. Ahmad; M. Isa (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
Variable speed drives (VSDs) are widely used in various applications mainly in process industry need constant rotational speed. It is developed from power electronic components thus saving energy in its operation. Unfortunately it is susceptible against power quality problem for example voltage sags. The VSD may be disruption or drop out when it is supplied by voltage sags and it is determined by sag characteristics. This study is to investigate effect of voltage sags Types I, II and III on VSD through laboratory testing. The voltage sags characteristics are generated from voltage sag generator (Shaffner 2100 EMC).  The effects are presented in susceptibility curves in disruption and drop out conditions. The curves resulted are evaluated by standard curve recommended. Test results show that voltage sag Type I cause the VSD disruption only, whereas two types sag other result in the VSD disruption and also drop out. Evaluation results explain  a few test points are in operation area for disruption condition whereas test points for dropping out far below the threshold recommended. Hence the VSD has good quality to voltage sags.